Teoria do domínio da organização como subespécie da teoria do domínio do fato e sua aplicabilidade ao ordenamento jurídico brasileiro - Dores, Marina Sanches Alencar (2023)
In the consideration of the traditional Theory of Crime, a tonic that holds extreme importance and deserved attention is the treatment dictated to the various actors involved in the criminal act. In this regard, in relation to crimes committed by more than one person, characterizing what is known as joint criminal conduct, the discussion that has been going on for years reflects on the doubt about the distinction between the authors of the crime and those who are considered mere accomplices in the criminal activity. Therefore, this essay aims to analyze the new form of criminality that afflicts Brazilian reality, aiming to demonstrate that the traditional objective-formal theory, still accepted in a majority in the national legal system, is increasingly inadequate. The purpose of this study is to reveal that the Theory of Organizational Domain, a sub-species of the Theory of Domain of the Fact, is suitable for application in crimes committed by both criminal organizations, such as the Primeiro Comando da Capital – PCC, as well as crimes committed by business organizations and legal entities. Thus, this paper aims to expose the best applicability of the Theory of Organizational Domination in contrast to traditional forms of attribution of authorship, which have long been used as the only solution to the issue of joint criminal conduct. Finally, the theme presented here is of fundamental importance to Brazilian criminal law, especially in the face of the modernization of criminal methods, particularly those practiced through organized sources of power